The Art of Intraoperative Glioma Identification - Zhang, Zoe Z.; Shields, Lisa B. E.; Sun, David A.; Zhang, Yi Ping; Hunt, Matthew A.; Shields, Christopher B. (Frontiers in Oncology, 2015)
A major dilemma in brain tumor surgery is the identification of tumor boundaries to maximize tumor excision and minimize postoperative neurological damage. Gliomas, especially low-grade tumors, and normal brain have a similar color and texture which poses a challenge to the neurosurgeon. Advances in glioma resection techniques combine the experience of the neurosurgeon and various advanced technologies. Intraoperative methods to delineate gliomas from normal tissue consist of 1) image-based navigation, 2) intraoperative sampling, 3) electrophysiological monitoring, and 4) enhanced visual tumor demarcation. The advantages and disadvantages of each technique are discussed. A combination of these methods is becoming widely accepted in routine glioma surgery. Gross total resection in conjunction with radiation, chemotherapy, or immune/gene therapy may increase the rates of cure in this devastating disease.